Cooking for Health: a healthy food budgeting, purchasing, and cooking skills randomized controlled trial to improve diet among American Indians with type 2 diabetes - Caitlin N. Hawley; Corrine M. Huber; Lyle G. Best; Barbara V. Howard; Jason Umans; Shirley A. A. Beresford; Barbara McKnight; Arlette Hager; Marcia O'Leary; Anne N. Thorndike; India J. Ornelas; Meagan C. Brown; et al. (BMC, 2021)
Abstract Background The prevalence of poor diet quality and type 2 diabetes are exceedingly high in many rural American Indian (AI) communities. Because of limited resources and infrastructure in some communities, implementation of interventions to promote a healthy diet is challenging-which may exacerbate health disparities by region (urban/rural) and ethnicity (AIs/other populations). It is critical to adapt existing evidence-based healthy food budgeting, purchasing, and cooking programs to be relevant to underserved populations with a high burden of diabetes and related complications. The Cooking for Health Study will work in partnership with an AI community in South Dakota to develop a culturally-adapted 12-month distance-learning-based healthy food budgeting, purchasing, and cooking intervention to improve diet among AI adults with type 2 diabetes. Methods The study will enroll 165 AIs with physician-diagnosed type 2 diabetes who reside on the reservation. Participants will be randomized to an intervention or control arm. The intervention arm will receive a 12-month distance-learning curriculum adapted from Cooking Matters® that focuses on healthy food budgeting, purchasing, and cooking skills. In-person assessments at baseline, month 6 and month 12 will include completion of the Nutrition Assessment Shared Resources Food Frequency Questionnaire and a survey to assess frequency of healthy and unhealthy food purchases. Primary outcomes of interest are: (1) change in self-reported intake of sugar-sweetened beverages (SSBs); and (2) change in the frequency of healthy and unhealthy food purchases. Secondary outcomes include: (1) change in self-reported food budgeting skills; (2) change in self-reported cooking skills; and (3) a mixed-methods process evaluation to assess intervention reach, fidelity, satisfaction, and dose delivered/received. Discussion Targeted and sustainable interventions are needed to promote optimal health in rural AI communities. If effective, this intervention will reduce intake of SSBs and the purchase of unhealthy foods; increase the purchase of healthy foods; and improve healthy food budgeting and cooking skills among AIs with type 2 diabetes - a population at high risk of poor health outcomes. This work will help inform future health promotion efforts in resource-limited settings. Trial registration This study was registered on ClinicalTrials.gov on October 9, 2018 with Identifier NCT03699709 .